The Regulation of Indigenous Peoples’ Usufruct Rights under Cameroonian Forestry Law: A Sustainable Participatory Approach (African Journal of Law and Politics, 2025)
The State of Cameroon plays a double role in sustainable forest resources governance, as both the owner and manager, which naturally limits efficiency and integrity. It has developed and refined its due role as neutral mediator, technical adviser, monitor, and rigorous regulator of sustainable forest resource management. Since indigenous peoples have the misfortune that their lands are found in resource rich areas, they are vulnerable to allocations to grantees or developers of government’s choice such as loggers, miners, and conservationist or plantation entrepreneurs; despite their legal right to participate in forest resource governance. As a matter of fact, Cameroon’s laws have failed to acknowledge indigenous customary land-holding as amounting to real property interests and accord protection only to private property, including cleared or cultivated or physically settled land with houses. In line with the fact that most of the indigenous customary estates are purposely held for non-permanent cultivation and is used collectively by indigenous people for hunting and gathering, the greater part of it is handed out without compensation. On the safeguard of the usufruct rights of indigenous peoples under the forestry laws in Cameroon, this paper adopts a doctrinal method, and arrives at the findings that the State lacks the legal capacity to sustainably manage, regulate or conserve its precious forest resources, and effectively engage the participation and consultation of indigenous peoples to defend their collective interests and maintain their usufruct rights as intrinsically linked to their fundamental rights to maintain and strengthen their distinct political, legal, economic, social and cultural development.